Cholinesterase-based biosensors - Štěpánková, Šárka; Vorčáková, Katarína (Journal of enzyme inhibition and medicinal chemistry, 2016)
Recently, cholinesterase-based biosensors are widely used for assaying anticholinergic compounds. Primarily biosensors based on enzyme inhibition are useful analytical tools for fast screening of inhibitors, such as organophosphates and carbamates. The present review is aimed at compilation of the most important facts about cholinesterase based biosensors, types of physico-chemical transduction, immobilization strategies and practical applications.
Keywords: cholinergní antagonisté; cholinesterases; biosensor; Cholinesterase Inhibitors; immobilization; transducers; zvířata; biosenzitivní techniky; Biosensing Techniques; Cholinesterases; Humans; cholinesterasové inhibitory; Applications; cholinesterasy; Cholinergic Antagonists; lidé; Animals